In-situ TEM Study of Dislocation Loop Evolution in Tungsten under Dual-ion Beam Irradiation - MA Pengfei1, LIU Yan2, CAO Liuxuan2, ZHANG Yapei1, LI Xiurui1, TIAN Wenxi1, QIU Suizheng1, SU Guanghui1 (Yuanzineng kexue jishu)
Fusion reactors are regarded as the ultimate source of energy for addressing future power problems. However, prior to the building of fusion power plants, a number of scientific obstacles including significant degradation of plasma-facing material (PFM). Due to its excellent irradiation resistance at high temperature, tungsten is considered a promising PFM for fusion reactor. The application of tungsten in fusion reactor faces stringent environmental challenges, primarily due to the substantial thermal loads, neutron flux, and gas atoms such as hydrogen and helium generated during fusion. Numerous studies have employed ion irradiation to simulate the service environment of PFM and to develop fusion reactor materials with strong irradiation resistance. High-energy ion irradiation induces lattice defects, including interstitial atoms and vacancies, which often aggregate into two-dimensional dislocation loops with Burgers vectors of 1/2<111> or <100> in body-centered cubic (BCC) materials. In the study of dislocation loops, the irradiation damage dose and damage rate significantly influence the formation and evolution of dislocation loops. Gas ion irradiation of tungsten materials exacerbates dislocation loop reactions, with the ratio of 1/2<111> to <100> dislocation loops varying with the irradiation damage dose. Current research on the irradiation resistance of tungsten mainly focuses on irradiation temperature, dose, and ion species effects of single ion beam or in-situ sequential beam irradiation, while studies on the synergistic effects by irradiation damage dose of simultaneous dual-ion beam irradiations in tungsten via in-situ TEM remain insufficient. Therefore, the present experiment primarily investigated the effects of varying irradiation damage doses on tungsten under high temperature conditions (700 °C) using dual-ion beam Kr+ & He+ irradiation. In-situ TEM was employed to observe the evolution of <100> and 1/2<111> dislocation loops under different irradiation damage doses, with a quantitative analysis of the dislocation loop evolution. In the unirradiated tungsten, no pre-existing dislocation loops are observed. As irradiation progresses, dislocation loops gradually nucleate, forming small-sized dislocation loops. The nucleation process spans the entire dislocation loop evolution loops process. As the dislocation loops grow, they interact and merge or absorb some point defects, eventually presenting as dislocation lines. Due to the entanglement of dislocation lines and loops, a dislocation network structure is formed. Increasing the irradiation damage dose also leads to the growth of 1/2<111> dislocation loops and the annihilation of <100> dislocation loops. This dislocation loop evolution mechanism can be attributed to two main factors: the reaction between 1/2<111> dislocation loops forming <100> dislocation loops and the reaction at specific locations and temperatures where <100> dislocation loops transform into 1/2<111> dislocation loops. The formation and annihilation of <100> dislocation loops under Kr+ and He+ dual-ion beam irradiation are expected to significantly impact the mechanical properties of tungsten. This study deepens the understanding of the microstructural evolution of irradiation-induced defects in tungsten, providing a fundamental basis for the application of tungsten in fusion reactor.